Teaching Thermodynamics and Kinetics Parameters in Electrochemistry with Reference to the Sabatier Principle and Volcano-Like Plots for the Oxygen Reduction Reaction at Modified Electrodes - Ureta-Zanartu, M; Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (American Chemical Society, 2024)
Energy conversion devices such as fuel cells, metal-air batteries, and electrolyzers have been envisaged as possible solutions for cutting down the continuous accumulation of greenhouse gases resulting from the combustion of fossil fuel. The bottleneck reaction for these devices is the oxygen reduction reaction (ORR) occurring at the cathode. The sluggish ORR force in the use of catalysts is mainly based on precious metals like platinum. Iron and cobalt macrocycle catalysts (MN4) have been widely studied as an economic alternative for replacing the expensive Pt0 at the cathode, which is the most active catalyst for the ORR and the industrial standard. Understanding the theoretical and experimental aspects behind this technology is a primary goal for human capital formation and educational purposes. Unfortunately, there is a lack of fundamentals behind the concepts of free energy, adsorption energy, and kinetics. Thermodynamic and kinetic parameters are confused and are wrongly cross-linked. The Sabatier principle and volcano plots are usually misinterpreted. In this propaedeutic work, thermodynamic and kinetic aspects are considered for the ORR at MN4 catalysts to provide a practical guide for students and teachers. © 2024 American Chemical Society and Division of Chemical Education, Inc.